UPAYA KONSERVASI MATA AIR MELALUI PENGHIJAUAN DENGAN PENANAMAN 1000 BIBIT POHON DI DESA TETEBATU SELATAN KECAMATAN SIKUR, LOMBOK TIMUR - Ahmad Jupri; Dina Ardiyanti Rukmana; Ismi Febriani; Nuraeni Nuraeni; Pahmi Husain; Eka S Prasedya; Tapaul Rozi (Universitas Mataram, 2022)
Spring water is a natural state of water resources that flows out of the aquifer to the ground surface so that it becomes a source of clean water that is useful for the needs of people. South Tetebatu Village is one of the villages in the Sikur District, East Lombok Regency which has many springs because it is under the foot of Mount Rinjani. The need for clean water will continue to increase over time, so it is necessary to make conservation efforts to maintain water availability. The purpose of this activity is to preserve the environment and maintain the availability of clean water sources. Planting tree seedlings as an environmental conservation measure in the village of South Tetebatu, Sikur District, East Lombok. This service method consists of a site survey, data collection, and demonstration. The survey was carried out to every location of springs in Tetebatu Selatan Village which are used by residents to meet their daily needs. Second, collecting data on the name and location of the springs and what the residents use the water for. Third, the demonstration by planting 1000 tree seedlings to maintain the existence of existing springs. The results of this activity indicate the number of springs in the village of South Tetebatu is four springs. Most locations that have springs in South Tetebatu is Lendang Penyonggok area. Water resources. The reforestation activities went smoothly. The enthusiasm of the people who take part in these activities is very high and increases public environmental awareness to maintain the availability of clean water and the preservation of the surrounding environment.